The Etruscan. - Waltari, Mika (Hauraki Publishing, 2016)
First published in 1956, The Etruscan is a fiction novel by Finnish author Mika Waltari. Beginning around 480 B.C., the story takes us on the spiritual journey of a young man named Lars Turms as he adventures through Ancient Greece to Sicily, Rome and, finally, Tuscany, searching for the meaning of life. He gradually becomes aware of his immortality and his duties to the future. Although set in ancient civilization, the book poses many of life's existential questions asked to this day, and the reader will find timeless answers to these timeless questions through the main character. -- Provided by publisher.